The Use of English Listening Lesson Library Online as Teaching Media by Vocational High School Teacher - Yulia Indriani; Effendi Limbong; Istanti Hermagustiana (EduLine: Journal of Education and Learning Innovation, 2024)
This study delves into the features of ELLLLO ( English Listening Lesson Library) used by the vocational high school teacher, with a focus on exploring her attitudes toward it through Makhlouf & Bensafi (2021) theory. This qualitative case study utilized semi-structured interviews and observations, collecting data from a vocational high school teacher at SMKN 3 Tenggarong through purposeful sampling. There are The five features used by teacher with different method and purposes concluded from the Observations and Interview. Then, Thematic analysis was employed to analyze the data to find the teacher;’s attitude. Then, the vocational teacher’s attitude towards using ELLLO in teaching listening was both positive and negative. She could provide receptive and productive skills in one media and it was easier for her to prepare for the class. The teacher’s attitude was also supported by her students' reactions who were more motivated to learn English using ELLLO. In contrast, the teacher feels upset to the pronunciation menu which is not yet available on ELLLO. The study found that ELLLO is an application that not only provides audio recording but also a grammar spot menu and quiz inside it. It appears that it was good to bridge the students’ and teachers’ needs at SMKN 3 Tenggarong.